2008
DOI: 10.1177/1076029607306397
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Aggregation and Activation in Thalassemia Major Patients in Indonesia

Abstract: Thromboembolic events and hypercoagulable state have been reported in patients with thalassemia. As platelets play an important role in the pathogenesis of thrombosis, the authors aimed to find the pattern of changes in platelet count, function and activation, and evidence of coagulation activation in patients with thalassemia major in Indonesia. A total of 31 patients with splenectomized and 35 patients with nonsplenectomized thalassemia major were enrolled in this study. Platelet count, platelet aggregation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Additionally, a previous study revealed that PLT activation, induced by ADP, is higher in splenectomized than in nonsplenectomized thalassemia patients, 69 aligning with our findings where both β-TDT groups exhibited higher ADPinduced PLT aggregation compared to the normal control. However, our study showed that PLT activation induced by collagen in splenectomized patients had lower maximum 70 This discrepancy might be attributed to iron overload conditions, as our splenectomy group displayed higher plasma ferritin levels, potentially affecting the PLT function via collagen induction.…”
Section: ■ Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, a previous study revealed that PLT activation, induced by ADP, is higher in splenectomized than in nonsplenectomized thalassemia patients, 69 aligning with our findings where both β-TDT groups exhibited higher ADPinduced PLT aggregation compared to the normal control. However, our study showed that PLT activation induced by collagen in splenectomized patients had lower maximum 70 This discrepancy might be attributed to iron overload conditions, as our splenectomy group displayed higher plasma ferritin levels, potentially affecting the PLT function via collagen induction.…”
Section: ■ Discussionsupporting
confidence: 93%
“…A chronic hypercoagulable state is related with PLT activation. , Therefore, to examine PLT activities, we performed PLT aggregation tests induced by adenosine diphosphate (ADP) or collagen and measured the percentage of maximum PLT aggregation. As shown in Figure A,B, the maximum ADP-induced PLT aggregation in the splenectomy group was significantly higher ( p -value < 0.01), while the nonsplenectomy group showed a slightly higher but not significant ( p -value = 0.93) compared to the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Tissue hypoxia due to chronic anemia may damage the endothelium causing interaction of platelets with the vessel wall. This results in the formation of circulating aggregates by the more active platelets while the less active ones are detected in vitro as poorly aggregable [ 16 , 19 ]. Orudzhev et al observed increased levels of circulating antiplatelet antibodies, immunoglobulins, and variable-sized immune complexes in their β-thalassemia patients and suggested their role in causing increased platelet disaggregation with resultant in vitro hypoaggregation of platelets [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…ADP secreted from granules is important in mediating the next steps of activation and aggregation, causing platelets to adhere to one another. Thalassemia patients have increased P-selectin expression on platelets and soluble P-selectin in plasma [ 17 , 24 , 27 ]. Herein, we provide additional data on the association of nitrite reductase activity of HbE with P-selectin expression on platelets.…”
Section: Discussionmentioning
confidence: 99%